2019
DOI: 10.3139/217.3717
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Hydrophobic Flat Sheet Membranes Based on a Recycled Polymer

Abstract: In this work, we used a recycled low-density polyethylene (LDPE) in order to prepare flat sheet membranes with different polymer concentrations (5 and 10%). The used chemical method for the membrane's preparation is the phase inversion. After obtaining the membranes, we characterized them by atomic force microscopy (AFM) and scanning electron microscopy (SEM) to study their structure and surface characteristics. Based on the SEM images, our membranes have a dense skin layer. In addition, we observed a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The increase in concentration affected the roughness on the surface, causing the hydrophilicity properties of the membrane to decrease. Ajari et al 30 reported the same thing in LDPE membranes, where an increase in polymer concentration from 5% to 10% led to an increase in the contact angle of the membrane due to increasing the roughness of the membrane surface.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The increase in concentration affected the roughness on the surface, causing the hydrophilicity properties of the membrane to decrease. Ajari et al 30 reported the same thing in LDPE membranes, where an increase in polymer concentration from 5% to 10% led to an increase in the contact angle of the membrane due to increasing the roughness of the membrane surface.…”
Section: Resultsmentioning
confidence: 70%
“…According to the results in Table 2, HDPE waste could be dissolved in toluene, xylene, and mineral oil. However, because the boiling point of xylene and toluene only ranged from 110–140 °C, 30 this solution could be very easily compacted when poured on a glass plate. As a result, this would certainly complicate the membrane casting process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many configurations of membranes can be seen such as hollow fiber membranes or flat membranes [28]. In this study, we prepared flat membranes from a waste of low density polyethylene (LDPE) as described elsewhere [29].…”
Section: Membrane Preparationmentioning
confidence: 99%
“…More specifically, researchers have sought to leverage hydrodynamic phenomena' simulation and modeling studies to optimize membrane distillation operating parameters [1][2][3][4][5]. Furthermore, the choice of membrane materials and fabrication processes have been widely explored to increase the permeate flux and mitigate fouling phenomena [6][7][8][9][10]. According to Culfaz et al [11], the helical configuration of the membrane promotes turbulence and therefore causes a significant reduction in concentration polarization.…”
Section: Introductionmentioning
confidence: 99%